Quantitative Comparative Analysis of the Endoscope-Assisted Expanded Retrosigmoid Approach and the Far-Lateral Approach to the Inframeatal Area: An Anatomic Study With Surgical Implications. Issue 3 (18th March 2023) - Revuelta Barbero, J. Manuel; Porto, Edoardo; Prevedello, Daniel M.; Noiphithak, Raywat; Yanez-Siller, Juan C.; Martinez-Perez, Rafael; Pradilla, Gustavo
Abstract : BACKGROUND: The inframeatal area (IFMA) is a complex anatomic region of the posterior cranial fossa. Given its deep-seated location, tumors involving the IFMA represent a surgical challenge. OBJECTIVE: To objectively compare the endoscope-assisted expanded retrosigmoid approach (ERSA) and the far-lateral supracondylar transtubercular approach (FLTA) to address the IFMA. METHODS: Anatomic dissections were performed on 5 cadaveric heads (10 sides). The ERSAs were performed before and after the FLTAs. The surgical exposure, surgical freedom, and angles of attack to the IFMA were measured and compared for each approach. In addition, 2 illustrative clinical cases are reported. RESULTS: Compared with FLTA, ERSA yielded a nonsignificantly smaller mean area of exposure, whereas FLTA provided a significantly larger mean area of surgical freedom, compared with ERSA ( P = .002). The mean horizontal and vertical angles of attack were significantly different between the approaches. In the vertical plane, FLTA yielded the broadest angle of attack at the root entry zone of the lower cranial nerves (CN; P < .004), whereas ERSA did so at the dural entry zone of CN VII/VIII ( P = .006). In the horizontal plane, FLTA achieved its broadest angle of attack at the root entry zone of the lower CNs ( P = 1.83) while ERSA at the dural entry zone of CN VII/VIII ( P = .37). CONCLUSION: ERSA and FLTA granted a comparable exposure with the IFMA. Although FLTA may afford a larger area of surgical freedom, ERSA may be a suitable alternative to approach the IFMA, particularly to reach the most medial and superior aspects of this region. Conversely, FLTA may facilitate access to more caudally targets.